The Effectiveness of Studying a Course in "Technology of Nanomaterials" on the Acquisition of Fundamental Knowledge and Attitudes Toward Nanotechnology - Malkawi, Amal (Jordan Journal of Educational Sciences, 2017)
This study aimed to identify the effectiveness of studying an introductory course in "Technology of Nanomaterials" on the acquisition of fundamental knowledge and attitudes towards nanotechnology among students of engineering materials at Balqa Applied University in Jordan. The sample consisted of (24) students enrolled in the course during the first semester of the academic year 2015-2016. To measure the students acquisition of fundamental knowledge of nanotechnology, a test consisted of (35) items was applied, and to determine students' attitudes, a questionnaire consisted of (29) items was applied to the same sample. The sample studied a course in Technology of Nanomaterials for (14) weeks; (3) hours a week. Then the two instruments were admistered as post tests. The results showed statistically significant differences in acquiring knowledge of and attitudes towards nanotechnology. The results also revealed a positive correlation between them